Implementation of Multiple Intelligences Approach Based On Batak Angkola Culture in Learning Thematic For Class IV SD Negeri 100620 Pargarutan Julu South Tapanuli District - Frida Marta Argareta Simorangkir; Darinda Sofia Tanjung (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
The purpose of this study is to describe the preparation, implementation and assessment related to the implementation of the Batak Angkola culture-based Multiple Intelligences approach in the thematic learning of grade IV SD 100620 Pargarutan Julu, South Tapanuli District. This research uses a qualitative research approach with descriptive research type. The subjects of this study were grade IV teachers and grade IV students. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques consist of data reduction, data display and conclusion drawing. The results showed that the implementation of the Multiple Intelligences approach in thematic learning in grade IV SD 100620 Pargarutan Julu, South Tapanuli Districttook place well. The teacher has used varied learning methods and strategies for the Batak Angkola culture, including using lecture and story methods for students who are superior in verbal-linguistic intelligence, demonstrations in ritual ablution for students who are superior in physical-kinesthetic intelligence. For students who excel in multiple intelligence, the teacher teaches with presentations that combine creative linguistic, mathematical and kinesthetic methods with creativity. The learning assessment is reviewed from 3 aspects namely; 1) cognitive by oral, written and assignment tests, 2) affective by observation and self-assessment, and 3) psychomotor with project and practice assignments. It can be concluded that the teacher has carried out activities to provide apperception and motivation and to carry out multiple intelligence-based activities to develop the nine types of intelligence, including: linguistic-verbal, mathematical-logical, visual spatial, kinesthetic, musical, interpersonal, intrapersonal, naturalist and existentialist. So with the implementation of the Multiple Intelligences approach, thematic learning is more fun and meaningful.